2007
DOI: 10.2746/042516407x236550
|View full text |Cite
|
Sign up to set email alerts
|

Alternative vaccination against equine botulism (BoNT/C)

Abstract: Recombinant Hc BoNT/C is an appropriate vaccine candidate to stimulate production of neutralising antibodies against botulinum neurotoxin C in horses and creates only minor local reactions at the injection site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, preclinical and clinical trials have shown that modifications to render the viral vectors replication-deficient still enable the vector to deliver antigen efficiently and generate protective immune responses against influenza [106][107][108][109][110][111][112][113] . The modified vaccinia virus Ankara (MVA) has been evaluated in preclinical experiments for delivery of influenza antigens [114] , but it has only been evaluated in clinical trials for delivery of HIV antigens, human papilloma virus, malaria, small pox and some cancers [115][116][117][118][119][120] , where it has been shown to generate humoral and cell-mediated immunity against the antigen delivered. We and others have shown that the human replication-defective Adenoviral 5 (Ad5) vector is able to efficiently deliver influenza antigens in preclinical studies to generate cross-protective humoral and cell-based immune responses protecting against lethal challenge with H5N1 virus [107,109] .…”
Section: Vector-based Vaccinesmentioning
confidence: 99%
“…However, preclinical and clinical trials have shown that modifications to render the viral vectors replication-deficient still enable the vector to deliver antigen efficiently and generate protective immune responses against influenza [106][107][108][109][110][111][112][113] . The modified vaccinia virus Ankara (MVA) has been evaluated in preclinical experiments for delivery of influenza antigens [114] , but it has only been evaluated in clinical trials for delivery of HIV antigens, human papilloma virus, malaria, small pox and some cancers [115][116][117][118][119][120] , where it has been shown to generate humoral and cell-mediated immunity against the antigen delivered. We and others have shown that the human replication-defective Adenoviral 5 (Ad5) vector is able to efficiently deliver influenza antigens in preclinical studies to generate cross-protective humoral and cell-based immune responses protecting against lethal challenge with H5N1 virus [107,109] .…”
Section: Vector-based Vaccinesmentioning
confidence: 99%
“…Animal botulism outbreaks are more common than in humans and can cause important productivity and economic losses [47,48]. In Europe, animal botulism is considered an emerging disease [49,50]. Contrary to humans, animal vaccines are available in the market from a number of different producers.…”
Section: Clostridium Botulinummentioning
confidence: 99%
“…Recombinant vaccines expressing the HC fragment of BoNT have also shown to be a potential alternative to toxoid vaccines. Horses vaccinated against recombinant HC BoNT/C were stimulated in the production of antibodies with few adverse reactions compared to the traditional toxoid vaccine [49]. Moreover, a multivalent vaccine comprised of HC-BoNT/A, HC- BoNT/B, and HC-BoNT/E protected mice from a multitoxin challenge [63].…”
Section: Clostridium Botulinummentioning
confidence: 99%